Experimental observation of parametric instabilities at laser intensities relevant for shock ignition. (31st March 2017) - Cristoforetti, G.; Colaïtis, A.; Antonelli, L.; Atzeni, S.; Baffigi, F.; Batani, D.; Barbato, F.; Boutoux, G.; Dudzak, R.; Koester, P.; Krousky, E.; Labate, L.; et al.
Abstract: We report measurements of parametric instabilities and hot electron generation in a laser intensity regime up to 6 × 10 15 W/cm 2, typical of the shock ignition approach to inertial fusion. Experiments performed at the PALS laboratory in Prague show that the incident laser energy losses are dominated by Stimulated Brillouin Scattering (SBS) rather than by Stimulated Raman Scattering (SRS) or Two-Plasmon Decay (TPD). Results are compared to hydrodynamics simulations using a code that includes self-consistent calculations of non-linear laser plasma interactions and accounts for the laser intensity statistics contained in the beam speckles. Good agreement is found for the backscattered SRS light, and for temperature and flux of hot electrons. The effect of high-intensity speckles on backscattered SRS is also underlined numerically and experimentally.